Au-delà de l’utopie : l’île comme révélateur de l’état socio-géopolitique du monde actuel
The island is a geographical reality, an allegory, a position, an ideological space: a visual motif. This land surrounded by water becomes a dream projection surface for utopias and for the experience of these earthly paradises. Not only places of tourism or fantasies of escape, they are heterotopies, “other spaces”, margins, exiles, elsewhere, an object of description and analysis. Because the island is not innocent, and beyond the exoticism that it embodies, the image of the island also reflects social and political positions, “islands-effects” transforming the geography explored from the islands into a philosophical, artistic, poetic and political approach. The island is the space in space, a project territory and unfinished space, which is the framework of many experiments and artistic productions questioning the singularity of these territories in a global perspective: a proposition of travel both theoretical and aesthetic.